Design of secondary wastewater treatment for rural China - Pan, Shan Shan (2010)
In this study, a rural village upstream of the Three Gorges Reservoir, the Jiaoyuan Village in Chongqing, China, was investigated to develop a feasible secondary wastewater treatment system. The constructed wetland was considered as the best choice for this application due to its effectiveness in secondary treatment, minimal operation and maintenance requirement, cost effectiveness and the ecological benefits. Two wetland designs were proposed to accommodate two different forms of household distribution. A layered subsurface flow constructed wetland (SSFCW) was designed to treat greywater generated from a single household and a surface flow constructed wetland (SFCW) was designed for clusters of households. The prototypes of both designs were constructed in NTU to test the treatment efficiency of COD, TN and TP using the synthetic greywater. Five wetland species, available both in Chongqing and Singapore, were chosen for the experiment, where Cyperus Alternifolius, Alocasia and Acorus calamus were planted in the SSFCW prototype and Thalia dealbata and Typha Angustifolia in the SFCW prototype. Three sets of pollutant loadings were applied in the experiment. Both the SSFCW prototype and the SFCW prototype showed good COD removal efficiency, up to 94.20% and 89.86% respectively. However, the systems failed to establish reliable and effective TN and TP treatments. Possible explanations are provided in the report.